Festival de Artes de São Cristóvão/SE : a percepção e o comportamento de consumo do público LGBTQIA+ - Santos, Elias Trindade dos (2024)
LGBTQIA+ consumer behavior has become an increasingly relevant topic in various market segments, including tourism with a focus on the LGBTQIA+ market and the growth of gay-friendly tourism or LGBT+ tourism. The LGBTQIA+ public is known for having a profile: most are single, have higher education and use their free time for leisure, culture and tourism (sebrae,2019), in addition to seeking travel experiences that meet their specific needs and desires, without prejudice and are welcoming to them (Attitude,2021). In this context, the São Cristóvão Arts Festival stands out as an event that has sought to become more inclusive and attractive to an audience that values diversity. Given this scenario, the general objective of this study was to analyze the service provided by the São Cristóvão Arts Festival and the consumption behavior of the LGBT+ public. The methodology used was descriptive, with a bibliographical survey and a case study, as well as a quantitative method. To collect the data, a questionnaire was administered to a sample of 66 LGBT+ people at the 2022 São Cristóvão Arts Festival. It is noteworthy that most people got to know FASC through a recommendation from friends. The main positive point of the FASC, according to the participants, was the food area. However, some aspects were pointed out as negative points, such as the toilets, signage, security and service. It was also possible to identify the profile of LGBT visitors to the festival, which is mainly made up of young university students, aged between 19 and 25, single and without an occupation. It was also possible to understand the behavior of these attendees, finding that the main motivation for going to the festival is the presence of musical attractions and the company of friends. The majority of participants attend the event with friends. Price and quality are the main factors considered when choosing to attend an event. Another important finding was that the FASC is a welcoming environment for LGBTQIA+ people, with most of them seeking service without prejudice and feeling comfortable expressing their sexuality at the FASC.